World Bank annual report 1993 - World Bank.; International Development Association; International Finance Corporation; Multilateral Investment Guarantee Agency (Washington, D.C. : World Bank, 1993)
This annual report which covers the period July 1, 1992, to June 30, 1993, has been prepared by the executive directors of both the IBRD and the IDA in accordance with the bye-laws of the two institutions.
Issues for 2004 accompanied by CD-ROM called: About the World Bank; includes organizational information, fiscal summaries, and tables previously included in chapter 6 and as appendixes in v. 2.; CD-ROM for 2005-<2006> called: World Bank annual report; includes organizational information, income by region, financial statements; CD-ROM no longer issued as of 2015 report; financial statements available online.
osc 22/03/17
Ref.
Keywords: Economic assistance; Banks and banking, International; Economic assistance; Economics